Re: Differential effect of assisted reproductive technology and small‐for‐gestational age on fetal cardiac remodeling. B. Valenzuela‐Alcaraz, F. Crispi, M. Cruz‐Lemini, B. Bijnens, L. García‐Otero, M. Sitges, J. Balasch and E. Gratacós. Ultrasound Obstet Gynecol 2017; 50: 63–70. (July 2017) - Patey, O.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2017; 50: 63–70